Dinâmica de Comunidades e Emissão de Metano por Cupins na Amazônia Central - Oliveira, João Rafael Alves de (Entomologia, 2021)
Termites (Insecta: Blattodea:Isoptera) are eusocial detritivorous insects, with species adapted to feed along the entire humification gradient. They are extremely abundant in the tropics and important ecosystem engineers. This thesis consists of three chapters. In the first, we investigate the relative contribution of the colonization and extinction processes of termite species in creating and maintaining patterns of spatial beta diversity. Termites were collected in three periods (2008, 2009 and 2014) in 30 plots of Reserva Ducke. We then calculated the vital rates (extinction and colonization) of the 112 found species and correlated with the average position of occurrence of the species along the environmental gradients. We found that although termite colonies die and are replaced over time, colonization occurs more commonly in places similar to what the species already does (0.17 < r2 < 0.40). On the other hand, extinction rates are not correlated with the environment, except for phosphorus to a lesser degree (r2 = 0.28), which suggests that the different pre-adaptations of species are crucial for species to be able to establish themselves in an environment, especially in the early stages of the colony. This differentiation maintains the patterns of beta diversity. In the second chapter, we address one of the aspects that highlight termites from other insects: the emission of methane (CH4), from the metabolic activity of symbionts that participate in the cellulose decomposition process in the termites digestive system. In the natural environment, the high CH4 production of these symbionts is counterbalanced by methanotrophic bacteria that use CH4 as a substrate for biomass incorporation and are more active in places with a high concentration of CH4, such as termite mounds. We measured emission of 9.97 CH4 nmol-1 s -1 from a nest of N. braziliensis. Based on the colony's biomass, we estimated that the colony produced around 36.58 CH4 nmol-1 s -1, which means that around three-quarters was filtered by the action of bacteria present in the nest and soil. We also report the emission by individuals of 14 species of termites from an Amazonian fragment. These data are important to better estimate the importance of termites in the overall CH4 budget. Finally, we describe a new species of Ruptitermes, from the subfamily Apicotermitinae, the least known taxonomically in the Neotropical region.
Keywords: Ecologia de Comunidades; Térmitas